Paul’s Economic Relationship With the Galatians: Burdensome Imposer or Welcomed Guest? - Borges, Jason (Tyndale bulletin, 2024)
How did Paul subsist during his travels in Galatia? This article contests Nasrallah’s claim that Paul placed burdens and imposed upon the local communities in Galatia akin to the Roman practice of requisitioning supplies and argues that the Galatians non-coercively welcomed Paul as a host and developed mutual relations with him. We first consider the social practices of Roman requisitions and ancient hospitality as suitable comparanda for interpreting Paul’s travel in Galatia. Then we examine two types of evidence clarifying the socio-economic aspects of Paul’s initial relationship with the Galatians—i.e., Paul’s recollections of his initial encounter with the Galatians (Gal 4:12-20) and subsequent traditions regarding the Galatians’ response to Paul. The evidence suggests that Paul’s relationship with the Galatians was, most probably, welcomed and mutual, not imposing or burdensome. This historical reconstruction contextualizes Paul’s subsequent letter and bears upon interpretations of Galatians.